The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.neuropharm.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin/orexin deficiency decreases cocaine abuse liability

Abstract: Compelling evidence indicates that hypocretin/orexin signaling regulates arousal, stress and reward-seeking behaviors. However, most studies on drug reward-related processes have so far described the effects of pharmacological blockers disrupting hypocretin/orexin transmission. We report here an extensive study on cocaine-related behaviors in hypocretin/orexin-deficient mice (KO) and their heterozygous (HET) and wildtype (WT) littermates. We evaluated behavioral sensitization following repeated administrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…indicates that this behavioral effect was mediated by a suppression of orexin cell activity elicited by the drug-context. This finding aligns well with previous studies that have reported reduced stimulus-driven cocaine-seeking following abstinence or extinction in orexin knockout mice (Steiner et al, 2018) or following either systemic or local pretreatment with an orexin-1 receptor antagonist (Smith et al, 2010;James et al, 2011;Mahler et al, 2013).…”
Section: Agonism Of Lha Group III Mglurs Reduces Orexin Cell Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…indicates that this behavioral effect was mediated by a suppression of orexin cell activity elicited by the drug-context. This finding aligns well with previous studies that have reported reduced stimulus-driven cocaine-seeking following abstinence or extinction in orexin knockout mice (Steiner et al, 2018) or following either systemic or local pretreatment with an orexin-1 receptor antagonist (Smith et al, 2010;James et al, 2011;Mahler et al, 2013).…”
Section: Agonism Of Lha Group III Mglurs Reduces Orexin Cell Activitysupporting
confidence: 92%
“…Therefore, some caution should be taken when considering how our electrophysiological findings relate to the reported behavioral data, and vice versa. However, we note that all published literature to date points to a large degree of overlap in the orexin system between rat and mouse in terms of topography (de Lecea et al, 1998;Sakurai et al, 1998;Sakurai et al, 1999;Stricker-Krongrad et al, 2002), projections and receptor distribution (Peyron et al, 1998;Chen et al, 1999;Marcus et al, 2001;Lin et al, 2002;Puskás et al, 2010;Ch'ng & Lawrence, 2015), electrophysiological properties (Yeoh et al, 2012) and role in reward-seeking behaviors (James et al, 2017b;Schmeichel et al, 2018;Steiner et al, 2018). Moreover, we have previously reported that plasticity at orexin cells occurs similarly between rats that self-administer cocaine and mice that receive experimenter-administered cocaine (as was the case here) on d1 of withdrawal (Yeoh et al, 2012).…”
Section: Group III Mglur Agonism Reverses Presynaptic Plasticity Withmentioning
confidence: 99%
“…Thus, higher expression and/or activation of these cells may attach greater motivational significance to cocaine‐associated stimuli and result in greater motivation (demand) for cocaine. A recent study in hypocretin/orexin knockout mice demonstrated that animals lacking the neuropeptide have reduced incubation of cocaine craving and do not reinstate drug‐seeking in response to cocaine‐paired cues . Greater numbers of cells promoting cue reactivity in high motivation animals may also explain our previous finding that animals with low α measured in BE have greater cue‐induced reinstatement of cocaine seeking .…”
Section: Discussionmentioning
confidence: 83%
“…We proposed that orexin signaling translates motivational drive into behavioral output (Mahler, Moorman, Smith et al, 2014), particularly in response to drug-associated cues and (Steiner, Rossetti, Sakurai et al, 2018). Greater numbers of cells promoting cue reactivity in high motivation animals may also explain our previous finding that animals with low α measured in BE have greater cue-induced reinstatement of cocaine seeking (Bentzley, Jhou & Aston-Jones, 2014).…”
Section: High Motivation Animals Have Greater Orexin Expression In Lamentioning
confidence: 84%